Knowledge Sharing as Key Driver for the Rise of Innovative Work Behavior - Riyadi Nugroho (Media Ekonomi dan Manajemen, 2023)
This study aims to examine the direct effect of job stress and transformational leadership on innovative work behavior. Furthermore, the purpose of this study is to investigate the role of knowledge sharing as a moderator in the relationship between job stress and transformational leadership on innovative work behavior. The data in this study were collected from 2,277 respondents who are teaching staff at higher education institutions in Indonesia. This study adopts a structural equation model approach with partial least squares testing (SEM-PLS) as a data analysis technique. This research proves that job stress and transformational leadership have a significant direct effect on innovative work behavior. This study also found that the link between job stress and transformational leadership and innovative work behavior is significantly mediated by knowledge sharing. The conclusion of this research reveals that knowledge sharing is a key driver of innovative work behavior among university academic staff in Indonesia. It is important to create a collaborative and supportive work environment, fosters creativity and innovation, and enables academic staff to stay up-to-date with the latest trends and developments in their field.